DETERMINAN STRUKTUR MODAL PADA BANK PERKREDITAN RAKYAT DI TANGERANG TAHUN 2013 - 2017 - Ar, Khorida; Utomo, Eko Narto (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2019)
This study aims to examine the effect of Current Ratio (CR), Fixed Assets (FA) and Tax on Debt to Equity Ratio (DER) of BPR Companies in Tangerang which are listed on the Indonesia Stock Exchange in 2013 to 2017. Data analysis techniques used in research this is a panel data regression model using E-Views software. The test results prove that CR (X1) has no effect on DER with a statistical t value of -1.668155 0.05. FA (X2) has a negative effect on DER with a t-value of -2.902127> t-table 1.97824. and a probability value of 0.0045 0.05. To find out the effect together, the F test is used where the results of CR, FA and Tax simultaneously affect the DER as indicated by an F statistic of 3.027314> F-table of 2.44 and an F-statistic probability value of 0.000019 <0.05, with a magnitude of the simultaneous effect of 45.53% can be seen from the R-squared value. While the remaining 54.47% is explained by other variables not examined.